Palliative care needs and health-related quality of life among patients with end-stage kidney disease on haemodialysis in a tertiary care hospital in Mumbai: a cross-sectional study - Shet, Neha Nitin; Solanki, Mridula; Lavangare, Sujata (International Journal Of Community Medicine And Public Health, 2026)
Background: End-stage renal disease (ESRD) is associated with substantial symptom burden, impaired health-related quality of life (HRQoL), and unmet palliative care needs. Despite the growing recognition of supportive care in nephrology, evidence from India remains limited. This study assessed HRQoL and palliative care needs among patients undergoing maintenance hemodialysis (MHD) and explored their relationship with symptom burden. Methods: A hospital-based cross-sectional study was conducted between June 2022 and January 2023 among 236 adults receiving MHD at tertiary care teaching hospitals in Mumbai, India. Palliative care needs were assessed using the palliative outcome scale-symptoms renal (POS-S Renal), while HRQoL was measured using the EuroQol five-dimensional five-level questionnaire (EQ-5D-5L) with the Indian value set. Sociodemographic and clinical data were collected through structured interviews and medical record review. The relationship between palliative care needs, symptom burden, and HRQoL was examined using correlation. Results: Participants had a median age of 64.5 years, and 63.6% were male. The median POS score was 16.0 (IQR: 12.0-23.0), indicating considerable unmet palliative care needs. Family anxiety, information needs, practical support, and symptom-related concerns were among the most prominent issues. The mean number of symptoms reported was 15.04±5.06, with dry mouth (91.5%), itching (83.1%), dry skin (82.2%), and fatigue being the most common symptoms. The median EQ-5D-5L utility score was 0.78, with older patients reporting poorer HRQoL. Higher POS scores were significantly associated with greater symptom burden and lower HRQoL. Conclusions: Patients receiving MHD experience substantial symptom burden, unmet palliative care needs, and reduced HRQoL. Early integration of multidisciplinary palliative care into routine nephrology services may improve symptom management, address supportive care needs, and enhance patient-centred outcomes.